Comparative transcriptome profiling and co-expression network analysis uncover the key genes associated with pear petal defense responses against Monilinia laxa infection - Aci, Meriem Miyassa; Tsalgatidou, Polina C.; Boutsika, Anastasia; Dalianis, Andreas; Michaliou, Maria; Delis, Costas; Tsitsigiannis, Dimitrios I.; Paplomatas, Epaminondas; Malacrinò, Antonino; Schena, Leonardo; Zambounis, Antonios (Frontiers in Plant Science, 2024)
Pear brown rot and blossom blight caused by Monilinia laxa seriously affects pear production worldwide. Here, we compared the transcriptomic profiles of petals after inoculation with M. laxa using two pear cultivars with different sensitivity to disease (Sissy, a relatively tolerant, and Kristalli, a highly susceptible cultivar). Physiological indexes were also monitored in petals of both cultivars at 2 h and 48 h after infection (2HAI and 48HAI). RNA-seq data and weighted gene co-expression network analysis (WGCNA) allowed the identification of key genes and pathways involved in immune and defense-related responses that were specific for each cultivar in a time-dependent manner. In particular, in Kristalli cultivar a significant transcriptome reprogramming occurred early at 2HAI and was accompanied either by suppression of key DEGs involved in modulation of any defense responses or by activation of DEGs acting as sensitivity factors promoting susceptibility. In contrast to the considerable high number of DEGs induced early in Kristalli cultivar, upregulation of specific DEGs involved in pathogen perception and signal transduction, biosynthesis of secondary and primary metabolism, and other defense-related responses was delayed in Sissy cultivar, occurring at 48HAI. The WGCNA highlighted one module that was significantly and highly correlated to the relatively tolerant cultivar. Six hub genes were identified withing this module, including three WRKY transcription factor encoding genes: WRKY 65 (pycom05g27470), WRKY (pycom10g22220), and WRKY28 (pycom17g13130), which may play a crucial role in enhancing the pear petals tolerance to M. laxa. Our results allow to gain insights in the interplay of the molecular mechanisms underlying immune responses of petals at pear -M. laxa pathosystem.